2017
DOI: 10.1002/mus.25760
|View full text |Cite
|
Sign up to set email alerts
|

Ventilator‐induced diaphragmatic dysfunction in MDX mice

Abstract: Short-term MV induces rapid diaphragmatic force loss and biochemical changes consistent with VIDD in mdx mice. This may have implications for the optimal use of intermittent MV in DMD patients. Muscle Nerve 57: 442-448, 2018.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 41 publications
1
13
0
Order By: Relevance
“…Protein was extracted from frozen diaphragm samples, and antibody dilutions were selected according to the manufacturers’ instructions. The following proteins were analyzed as previously described: (1) total and phosphorylated (Tyr705) forms of STAT3 (clones 124H6 and D3A7, Cell Signaling, USA); (2) carbonylated proteins (Oxyblot Protein Oxidation Detection Kit, Millipore, Germany) and 4-hydroxynonenal (4-HNE; R&D Systems, USA) as indices of oxidative stress; and (3) LC3B-I and LC3B-II levels (clone D11, Cell Signaling, USA) as indices of autophagy [8, 18, 19]. Immunoreactive bands were visualized using enhanced chemiluminescence and Ponceau red for protein loading.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Protein was extracted from frozen diaphragm samples, and antibody dilutions were selected according to the manufacturers’ instructions. The following proteins were analyzed as previously described: (1) total and phosphorylated (Tyr705) forms of STAT3 (clones 124H6 and D3A7, Cell Signaling, USA); (2) carbonylated proteins (Oxyblot Protein Oxidation Detection Kit, Millipore, Germany) and 4-hydroxynonenal (4-HNE; R&D Systems, USA) as indices of oxidative stress; and (3) LC3B-I and LC3B-II levels (clone D11, Cell Signaling, USA) as indices of autophagy [8, 18, 19]. Immunoreactive bands were visualized using enhanced chemiluminescence and Ponceau red for protein loading.…”
Section: Methodsmentioning
confidence: 99%
“…Primer sequences for genes involved in STAT3 activation (IL-6), the ubiquitin-proteasome pathway of proteolysis (Atrogin1, MuRF1), metabolism (SIRT1), autophagy (LC3B, Gabarapl1), and myosin heavy chain (MyHC) isoforms (1, 2a, 2x, embryonic, neonatal) are shown in Additional file 1: Table S1. The data are expressed as n -fold change relative to the average CTL group value according to the standard ΔΔ CT method [8, 18, 19].…”
Section: Methodsmentioning
confidence: 99%
“…Once activated, pSTAT3 dimerizes and enters the nucleus to activate transcription of various genes (Figure 1). STAT3 signaling has been shown to be activated in skeletal muscle and promotes skeletal muscle atrophy in muscle diseases, such as Duchenne muscular dystrophy (DMD), and Merosin-deficient congenital muscular dystrophy (MDC1A), as well as cancer and sepsis [7,8,9]. In addition to skeletal muscles, STAT3 signaling has been shown to play critical roles in both vascular and central nervous systems, thus directly and indirectly contributing to muscle health [10,11,12,13].…”
Section: Introductionmentioning
confidence: 99%
“…When DMD is coupled with MV for respiratory support, a more progressive pathology could theoretically ensue. In this issue of the journal, Liang and colleagues investigate the impact of MV in the context of an underlying neuromuscular disease, where the widely used dystrophic mouse model ( mdx ) was subjected to a brief 6‐hour period of MV . The authors hypothesized the previously reported features associated with VIDD (i.e., oxidative stress, upregulation of proteolytic and catabolic skeletal muscle pathways, and muscle weakness) were also present in the mdx mouse diaphragm after MV.…”
mentioning
confidence: 99%
“…In their work, the Liang et al . also identify the experimental MV duration as clinically analogous to nocturnal ventilation . Nocturnal noninvasive ventilation (NIV) is indicated in DMD patients with evidence of sleep‐disordered breathing or hypoventilation, and, in conjunction with airway clearance assistance and lung volume recruitment therapy, it forms the cornerstone of current respiratory management of DMD .…”
mentioning
confidence: 99%